Dr. Aamod Rao — Deep Plane Facelift — Mumbai - Rao, Aamod (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Aamod Rao, practicing in Mumbai, India. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003081; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; india; mumbai